Axillary surgery in breast cancer: primary results of the INSEMA trial - Reimer, Toralf; Stachs, Angrit; Veselinovic, Kristina; Kühn, Thorsten; Heil, Jörg; Polata, Silke; Marmé, Frederik; Müller, Thomas; Hildebrandt, Guido; Krug, David; Ataseven, Beyhan; Reitsamer, Roland; et al. (The New England journal of medicine, 2025)
This randomized trial involving patients with clinically node-negative, T1 breast cancer showed that the omission of axillary surgery was noninferior to sentinel-lymph-node biopsy.